2020
DOI: 10.1111/tid.13368
|View full text |Cite
|
Sign up to set email alerts
|

Matched retrospective study of infective endocarditis among solid organ transplant recipients compared to non‐transplant: Seven‐year experience in a US Referral Center

Abstract: Although infection accounts for a substantial burden of morbidity and mortality among solid organ transplant (SOT) recipients, infective endocarditis (IE) remains a relatively uncommon complication. It has been shown that the observed incidence of IE in SOT patients ranges from 1% to 1.7%, 1,2 which is markedly higher than the 5-7.9 cases per 100 000 reported in non-SOT. 3 Recent studies in non-SOT patients show a changing epidemiology characterized by an increase in incidence of IE 4 with concomitant increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 17 publications
(35 reference statements)
5
16
1
Order By: Relevance
“…In contrast with what has been reported for SOTRs in one study [ 21 , 26 ], but consistent with what was found in another [ 21 ], we found no case of fungal endocarditis. The undocumented cases in our study survived for more than seven years after an empiric antibiotic treatment, making a fungal origin of the infection highly unlikely.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast with what has been reported for SOTRs in one study [ 21 , 26 ], but consistent with what was found in another [ 21 ], we found no case of fungal endocarditis. The undocumented cases in our study survived for more than seven years after an empiric antibiotic treatment, making a fungal origin of the infection highly unlikely.…”
Section: Discussionsupporting
confidence: 91%
“…In that respect, the epidemiology in our study is closer to that of the general population [1]. We found that digestive bacteria predominate, with Enterococci as the most frequent pathogen, as previously described in SOTRs [14][15][16][17][18][19][20][21]. A hypothetical mechanism, in the absence of an identified digestive gateway (colonoscopy was performed in most of the cases where a digestive bacterium was identified, even though we did not collect the results of this exam in our study), could be the alteration of the gut microbiota by the combination of antibiotic treatments frequently used after transplantation, and of immunosuppressive drugs.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast with what has been reported for SOTRs in one study [21,26] but consistent with what was found in another [21] we found no case of fungal endocarditis. The undocumented cases in our study survived for more than seven years after an empiric antibiotic treatment, making a fungal origin of the infection very unlikely.…”
Section: Discussionsupporting
confidence: 91%
“…In that respect the epidemiology in our study is closer to that of the general population [1]. We found that digestive bacteria predominate, with Enterococci as the most frequent pathogen as previously described in SOTRs [15][16][17][18][19][20][21]14,21]. A hypothetical mechanism, in the absence of an identified digestive gateway (colonoscopy was performed in most of the cases where a digestive bacterium was identified, even though we did not collect the results of this exam in our study), could be the alteration of the gut microbiota by the combination of antibiotic treatment frequently used after transplantation, and of immunosuppressive drugs.…”
Section: Discussionsupporting
confidence: 73%
“…Bacteremia, a predisposing factor for developing IE, may occur more frequently in immunosuppressed individuals, such as patients who have undergone solid organ transplantation [ 3 ]. Interestingly, IE in liver transplant recipients has not been adequately described, even though there are isolated reports of such cases and there are large registries of patients with infective endocarditis which have attempted to characterize these patients, and yielded only a few patients at a time [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%